ANALISIS HUMAN RELATION, PERILAKU INDIVIDU DAN ETOS KERJA TERHADAP PENINGKATAN KINERJA PEGAWAI PT PERKEBUNAN NUSANTARA IV REGIONAL I MEDAN - Mia Oktavia; Eli Delvi; Emi Wakhyuni (CV. ALIM'SPUBLISHING, 2024)
Employee performance is an important factor that must receive serious attention for human resource management at PT Perkebunan Nusantara IV Regional I Medan. The level of success of a company is largely determined by the abilities of the employees in the company. This research aims to find out whether human relations, individual behavior and work ethic have an influence. The information analysis technique used is an associative research method with the help of the SPSS version 19 program. This research uses multiple linear regression analysis. The sample in this study was 55 respondents. Collecting preliminary information using a questionnaire. The results of the research show that human connection has a partially positive and significant effect on the performance of PT Perkebunan Nusantara IV Local I Medan employees. Individual behavior has a partially positive and significant effect on the performance of PT Perkebunan Nusantara IV Local I Medan employees. Work ethic has a partially positive and significant effect on the performance of PT Perkebunan Nusantara IV Provincial I Medan employees. Human connection, individual behavior and work ethic simultaneously have a positive and significant effect on the performance of PT Perkebunan Nusantara IV Provincial I Medan employees. The changed R Square value is 0.731 which can be called the coefficient of determination, which in this case means that 73.1% of employee performance can be obtained and explained by human connection, individual behavior and monkey ethos while the remaining 26.9% is explained by other factors or variables outside the research model.